Enabling a family caregiver-led assessment of support needs in home-based palliative care: Potential translation into practice. - Aoun, Samar; Toye, Christine; Deas, Kathy; Howting, Denise; Ewing, G.; Grande, G.; Stajduhar, K. (2015)
BACKGROUND: Systematic assessment of family caregivers' support needs and integrating these into service planning according to evidence-based research are vital to improving caregivers' outcomes and their capacity to provide care at end of life. AIM: To describe the experience with and feedback of nurses on implementing a systematic assessment of support needs with family caregivers in home-based palliative care, using the Carer Support Needs Assessment Tool. METHODS: This study was conducted during 2012-2014 in Silver Chain Hospice Care Service in Western Australia. This article reports on one part of a three-part evaluation of a stepped wedge cluster trial. Forty-four nurses who trialled the intervention with 233 family caregivers gave their feedback via surveys with closed- and open-ended questions (70.5% response rate). Analyses of quantitative and qualitative data were undertaken. RESULTS: The feedback of nurses was overwhelmingly positive in terms of perceived benefits in comparison to standard practice both from the family caregiver and service provider perspectives. Using the Carer Support Needs Assessment Tool was described by nurses as providing guidance, focus and structure to facilitate discussion with family caregivers and as identifying needs and service responses that would not otherwise have been undertaken in a timely manner. CONCLUSION: Our study has successfully addressed the call for alternatives to the professional assessment paradigm using the Carer Support Needs Assessment Tool approach as a caregiver-led intervention facilitated by health professionals. Integrating the Carer Support Needs Assessment Tool in existing practice is fundamental to achieving better caregiver outcomes.